2007
DOI: 10.4103/0028-3886.35692
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in rhinocerebral mycosis

Abstract: Rhinocerebral mycosis is associated with high mortality in spite of aggressive therapy. Intracranial extension with focal neurological deficits is a major predictor of mortality in rhinocerebral mycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…3 Commonly, mucormycosis has shown an equal sex distribution, although a recent review of all published cases of pulmonary mucormycosis showed a male-to-female ratio of 3:1. 142 Mortality rate is higher than 50% with an incidence ranging from 62.5% in rhino-cerebral form 143 to 100% in disseminated form. 140 Its high morbidity and mortality rates are related to its capacity for rapidly vascular invasions, with subsequent tissue necrosis and infarction.…”
Section: Discussionmentioning
confidence: 99%
“…3 Commonly, mucormycosis has shown an equal sex distribution, although a recent review of all published cases of pulmonary mucormycosis showed a male-to-female ratio of 3:1. 142 Mortality rate is higher than 50% with an incidence ranging from 62.5% in rhino-cerebral form 143 to 100% in disseminated form. 140 Its high morbidity and mortality rates are related to its capacity for rapidly vascular invasions, with subsequent tissue necrosis and infarction.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs primarily in decompensated patients with diabetes of both types, and in immunocompromised patients, particularly in those with neutropenia or in transplant recipients treated with corticosteroids. Mucorales by regulating cause lesions in pre‐disposed patients (Warnock and Richardson, 1982;Rinaldi, 1994; Eucker et al , 2001; Damante and Fleury, 1998; Jayalakshmi et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[18] In a study of 38 patients with rhinocerebral mycosis, 47% died; the predictors of mortality were elderly age, intracranial extension, and immunocompromised state. [15] In view of the small number of cases in our study, we could not ascertain the prognostic factors.…”
Section: Discussionmentioning
confidence: 88%